A The Threat of Agricultural Land Conversion to Food Security and Self-Sufficiency in Karawang Regency, Indonesia - Dana Pranata (Marcapada: Jurnal Kebijakan Pertanahan, 2026)
This study examines the threats posed by agricultural land conversion and analyzes the strategic role of intelligence agencies in mitigating these risks. Employing a qualitative case study approach in Karawang Regency, the research demonstrates that uncontrolled land conversion directly leads to diminished harvest areas, declining rice production, severe soil degradation, and heightened socio-economic pressures on rural communities. Furthermore, weak inter-agency coordination, ineffective law enforcement, and a lack of real-time spatial data accelerate productive land loss. This institutional gap triggers widespread farmer migration, food price inflation, social inequality, and land-access conflicts. To address these vulnerabilities, intelligence institutions play a pivotal role by implementing systematic field data collection, trend analysis, and early warning systems. These measures intercept illicit conversions and support targeted mitigation policies, including farmer capacity building, intervention mapping, and cross-sector collaboration. Ultimately, strategic intelligence serves as a critical instrument for projecting food availability, monitoring supply stability, and structuring crisis mitigation to secure sustainable food self-sufficiency in Indonesia.